Effects of Betahistine on Vestibulo-Ocular Reflex in normal healthy adults: a randomized double-blind, placebo-controlled trial - Wan Hassan, Wan Ahmad Amiruddin; Mohd Nasir, Khairul Ridhwan; Jamaluddin, Saiful Adli; Mohammad Aidid, Edre; Al- Hadeethi, Yahia F. Hussein (2022)
Introduction Vertigo, or the perception of a spinning sensation, is a common symptom experienced by patients who are referred to Otorhinolaryngology clinics. Betahistine is a medication that has been widely used to treat vertigo and its accompanying symptoms. However, the effects of this medication on the vestibulo-ocular reflex (VOR) are still unknown. Initially, it was assumed that betahistine should be discontinued prior to any vestibular tests, particularly the video head impulse test (vHIT).